Does the coingestion of carbohydrate and amino acids improve recovery from endurance exercise? - Saunders, M. (The Physician and Sportsmedicine, 2009)
The objectives of the study were to compare the effects of isocaloric carbohydrate (CHO) and carbohydrate/amino acid (CHO+AA) beverages on exercise performance and fatigue during a period of consecutive-day exercise training. This study demonstrates the importance of protein/amino acids for recovery in endurance athletes. (Original Article: Skillen, R.A., Testa, M., Applegate, E.A., Heiden, E.A., Fascetti, A.J., Casazza, G.A. Effects of an amino acid-carbohydrate drink on exercise performance after consecutive-day exercise bouts)